Pengoptimalan Biaya Pengiriman Barang Pada PT. Nias Express Dengan Menggunakan Metode North West Cornerv - Defriman Waruwu (STMIK Budi Darma, 2018)
PT. Nias Express is a company engaged in the delivery of goods. With the aim of providing servants to the owner of goods by guaranteeing the integrity and security of goods in the purpose of increasing the development of the company in the delivery of goods requires the company to be able to provide shipping services for consumers to support better shipping transactions. The Noerth west corner method is one method chosen by the author in solving problems that occur at PT. Nias Express, wherein the method, the calculation is done by starting from the edge to the fishery, using the need table and delivery table, so that optimization costs can be increased and not only when that is all, with the use of this method, the authors hope to increase service in shipping goods. Of the several problems that occur and are often experienced by PT. Nias Express is a cost that is unexpected, shipping and costs that are used in excess and uncontrolled expenditures used in shipping goods, with such problems, in need of systematic preparation in handling costs and shipping goods to arrive safely at destination.